KEBUGARAN JASMANI DAN WAKTU PEMULIHAN TEKANAN DARAH ATLET BOLA BASKET PUTRA PUSAT PENDIDIKAN DAN LATIHAN OLAHRAGA PELAJAR (PPLOP) JAWA TENGAH DENGAN PEMBERIAN MINUMAN SARI BIT MERAH (BETA VULGARIS)DAN TERONG BELANDA (CYPHOMANDRA BETACEA SENDTN) - Eka Waskito, Rizka Aprilia; Tursilowati, Susi; Setiadi, Yuwono (JURNAL RISET GIZI, 2017)
Background: The maximum performance an athlete achieves is determined by health factors, fitness, and transition phase/recovery. The recovery period is the body's energy restoration, and muscle tissue repair after exercise. Competition in the sport, making athletes look for supplements that can extend endurance, speed recovery, and improve the appearance of athletes. Consumption of bits regularly can help exercise longer without feeling fatigue and improve the ability to do business with high intensityObjective: Knowing the physical fitness and time of blood pressure basketball men’s athlete student center for training and sport exercise (PPLOP) of central java with drink red beetroot (Beta vulgaris) and terong belanda (Cyphomandra betacea Sendtn) juiceMethods: Type of research True Experimental Design with Randomized Repeated Measure Control Group Design design. The respondents of 17 bollabasket athletes were divided into control and treatment groups. Physical fitness (VO2max) is measured twice with a Multistage fitness test, and blood pressure is measured five times with a digital sphgmomanometer before and after exercise. Data analysis with ANOVA Repeated Measure test was controlled by control variable.Results: There was no significant difference of VO2max (p=0,814) in treatment group (49,28 ml/kgBB/min) and control group (46,13 ml/kgBB/min). There was no significant difference in the rate of recovery of systolic blood pressure (p=0.493) in the treatment group (5 minutes) and control group (7.47 minutes). There was no significant difference in the rate of recovery of diastolic blood pressure (p=0.566) in the treatment group (4.75 minutes) and control group (7 minutes).Conclusion: Giving red beetroot and terong belanda juice did not significantly affect in VO2max (p> 0,05) and blood pressure recovery time (p> 0,05). Increased VO2max and blood pressure recovery time was higher in the treatment group. It is recommended that research be carried out over a longer period of time, larger sample quantities and larger doses.